Current Knowledge on Inherited Platelet Function Disorders - Nani Jung; Ye Jee Shim (The Korean Society of Pediatric Hematology-Oncology, 2020)
Inherited platelet function disorders (IPFDs) are rare and underdiagnosed in individuals with clinically significant bleeding diathesis. IPFDs are classified according to the causative molecular defects involved in the process of primary hemostasis of platelets, which include the following: 1) adhesion (e.g., Bernard?Soulier syndrome and pseudo-von Willebrand disease), 2) activation (e.g., adenosine diphosphatase receptor defect and thromboxane A2 receptor defect), 3) signal transduction and granule secretion (e.g., gray platelet syndrome, Paris?Trousseau/Jacobsen syndrome, Chediak?Higashi syndrome, and Hermansky?Pudlak syndrome), 4) aggregation (e.g., Glanzmann thrombasthenia), and 5) procoagulant activity (e.g., Scott syndrome). Patients with IPFDs typically present with unexpected mucocutaneous bleeding during early childhood. The diagnosis of these conditions requires several laboratory tests including complete blood cell count, peripheral blood smear, platelet function analysis, light-transmission aggregometry, flow cytometry, electron microscopy, and genetic analysis. Platelet transfusion has been the mainstay of treatment. However, antifibrinolytics, desmopressin, and recombinant activated factor VII are also effective when used as a monotherapy or adjunctive therapy. Importantly, the prevention of bleeding event is the most basic strategy in the management of IPFDs. This review aimed to assess the normal platelet physiology and summarize the current knowledge about the molecular defects, diagnostic evaluation, and treatment strategies of the respective IPFDs. If the cause of the bleeding tendency is difficult to identify, IPFDs should be considered.